Experimental analysis and increasing the energy efficiency of PV cell with nano-PCM (calcium carbonate, silicon carbide, copper). (2021) - Senthil Kumar, K.; Ashwin Kumar, H.; Gowtham, P.; Hari Selva Kumar, S.; Hari Sudhan, R.
Abstract: The electrical efficiency of the photovoltaic PV panel depends heavily on its temperature. The electrical output reduces as the temperature of the PV rises. The use of PCM content for phase change is now one of the most important methods for minimizing and controlling the temperature of PV panels and increasing their electrical performance. Current research is based on experimental studies of the impact on the thermal behavior and electrical efficiency of PV panels utilizing Copper (Cu), Silicon Carbide (Sic), Calcium Carbonate (Cc). The correct test set-up was planned to continue and the prototypes have been developed and tested. A transient energy balance is also pre-sent for thermal evaluation. A transient energy balance is also pre-sent to determine the thermal behavior of the system and to compare it with electrical outputs. An effective prototype design was conceived and two designs were built and evaluated to continue. The prototype 1 consists of a frame, a photovoltaic panel and an electrical circuit with a specified charge Prototypes 2 was built with an aluminum container connected to the rear of PV plate, which contains the combined PCM. It has been shown that the electrical performance of PV panels improved by an average of 2.8 per cent when used as a normal and by an average of 4.3 per cent when used as a combined PCM. These changes as well as the underlying actions have been shown.